Diagnostic accuracy of cytology and urine methylation test in patients with non-muscle invasive bladder cancer: a systematic review and meta-analysis - Yao, Zhuoyue; Wang, Tao; Liu, Jingpeng; Zhou, Zhongbao; Zhang, Yong (Frontiers in Oncology, 2024)
BackgroundMultiple clinical studies have demonstrated the numerous advantages of urine methylation test over cytology for monitoring patients with non-muscle invasive bladder cancer (NMIBC) following surgery. This research aims to provide a systematic review and meta-analysis to evaluate the efficacy and limits of urine methylation test in the clinical management of NMIBC.MethodsThis research was carried out by conducting a comprehensive search of clinical trials comparing cytology and urine methylation test for NMIBC follow-up using databases such as PubMed, Embase, Web of Science, and the Cochrane Library up until May 2023, including references from relevant articles. The study is registered on PROSPERO with ID CRD42023398969.ResultThis study comprised six studies with a total of 1676 patients. The analysis revealed that the AUC of urine methylation test had a greater AUC than that of the cytology examination (0.89 vs 0.71). In post-operative follow-up of patients with NMIBC, the urine methylation test demonstrated a significant sensitivity (0.69 vs 0.52), but with lower specificity (0.87 vs 0.93) than cytology examination.ConclusionThe urine methylation test and cytology examination have both shown strong diagnostic performance in screening for NMIBC patients. However, urine methylation test outperforms cytology examination in terms of accuracy and sensitivity.Systematic review registrationPROSPERO, identifier CRD42023398969.